PREPARASI NANOPARTIKEL KITOSAN-TPP/ EKSTRAK ETANOL DAGING BUAH MAHKOTA DEWA (Phaleriamacrocarpa (Scheff) Boerl) DENGAN METODE GELASI IONIK - Rauhatun Napsah; Iis Wahyuningsih (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2014)
Abstract: Mahkota dewa (Phaleria macrocarpa (Scheff) Boerl) is one of the plants frequentlyused as anticancer. But mahkota dewa extract have a high toxicity. One of certain effort thatcould reduces the toxic effect of medicine is nanoparticle decivery. The aims of this study were tomake nanoparticle from chitosan-mahkota dewa extract using TPP as a cross linker and todetermine it's particle size, zeta potential, loading capacity and loading efficiency. Chitosannanoparticles extract of Phaleria macrocarpa fruits with TPP as cross linker by ionic gelationmethod. Chitosan was dissolved in acetic buffer solution at pH 4 with various concentrations(0.045 and 0.09 % b/v), meanwhile tripolyphosphate (0.009 dan 0.018 % b/v) with volumecompare (5 : 1). The characterizations of chitosan nanoparticles of extract were determined bymeasure its particle size, zeta potential, loading capacity, and determining efficiency valuenanoparticle process formed. The results showed that the most stable extract were onconcentration 0.68 and 0.9 mg/ml (kitosan 0.09 % b/v, TPP 0.018 % b/v) with 350 rpm stirringspeed. The average of nanoparticle size were 190.9 and 162.87 nm. The zeta potential were 48.5mV and 60.86 mV, the loading capacity were 2.96 and 5.33 %, than the loading efficiency were35.75 and 45.26 %. Preparation of chitosan-extract of mahkota dewa fruits by ionic gelationmethod can produced nanoparticles and has a short range of size distribution, grade ofuniformity and good stability.Key words: Mahkota dewa, nanoparticles, chitosan, ionic gelation.